(untitled) (Academia Science Repository, 2023)
Immunological and biochemical indicators of natural resistance of Karakul lambs of different colors were studied. According to the results of the study, certain immune and biochemical indicators showed that the natural resistance of lambs of a light brown color exceeds that of lambs of black and gray color.